Capacitive performance of vertically aligned reduced titania nanotubes coated with Mn2O3 by reverse pulse electrodeposition. Issue 41 (25th June 2018) - Samsudin, Nurul Asma; Zainal, Zulkarnain; Lim, Hong Ngee; Sulaiman, Yusran; Chang, Sook-Keng; Lim, Ying-Chin; Ayal, Asmaa Kadim; Mohd Amin, Wardatun Nadrah
Abstract : Mn2 O3 was coated onto reduced titania nanotubes by reverse pulse electrodeposition, showing smooth and homogenous deposits without covering the opening of the nanotubes. Abstract : In this study, a composite material, manganese oxide/reduced titania nanotubes (Mn2 O3 /R-TNTs), was synthesized through incorporation of Mn2 O3 onto R-TNTs via the reverse pulse electrodeposition technique. The influence of pulse reverse duty cycles on the morphological, structural and electrochemical performance of the surface was studied by varying the applied duty cycle from 10% to 90% for 5 min total on-time at an alternate potential of −0.90 V ( E on ) and 0.00 V ( E off ). FESEM analysis revealed the uniform deposition of Mn2 O3 on the circumference of the nanotubes. The amount of Mn2 O3 loaded onto the R-TNTs increased as a higher duty cycle was applied. Cyclic voltammetry and galvanostatic charge–discharge tests were employed to elucidate the electrochemical properties of all the synthesized samples in 1 M KCl. The specific capacitance per unit area was greatly enhanced upon the incorporation of Mn2 O3 onto R-TNTs, but showed a decrease as a high duty cycle was applied. This proved that low amounts of Mn2 O3 loading enhanced the facilitation of the active ions for charge storage purposes. The optimized sample, Mn2 O3 /R-TNTs synthesized at 10% duty cycle, exhibited high specific capacitance of 18.32 mF cm −2 at a current density of 0.1 mA cm −2 obtained from constant current charge–discharge measurements. This revealed that the specific capacitance possessed by Mn2 O3 /R-TNTs synthesized at 10% duty cycle was 6 times higher than bare R-TNTs.